Revisiting the privacy calculus: Why are consumers (really) willing to disclose personal data online? - Teresa Fernandes (2021)
With the digital age, businesses are increasingly collecting consumers' data, which is raising privacy issues. Existing research has been dominated by the rational-based privacy calculus theory, which overlooks the role of irrationality and contextual factors. This study accounts for the influence of both rational (benefits and costs) and irrational (habits) factors in the disclosure decision-making process, while considering the moderating role of context sensitivity. Data gathered from 956 consumers who disclosed personal data with self-selected companies partially supports the context-dependence of data disclosure and reveals that, although consumers do face a trade-off between perceived benefits and privacy loss, habit plays a dominant role. The study extends the privacy calculus theory and provides insights for businesses aiming to collect consumers' data across industries.